Reducing Patient Waiting Time in Radiology: A Structural Equation Modelling Analysis - Mark Alipio (JPAIR, 2020)
Short patient waiting time is an important marker of effective healthcare service delivery. However, radiology, a first-line diagnostic specialty, is currently challenged in providing prompt care to patients owing to the complexity of its administrative process and increasing patient demand. This study sought to develop a framework for reducing patient waiting time in radiology departments of 10 government hospitals in the Philippines. A total of 350 radiology patients in November 2019 participated, and survey questionnaires were used to elicit data. Using structural equation modeling, the study reported that healthcare providers’ punctuality had the greatest impact on patient waiting time. Administrative processes completely mediate the effects of patient flow on patient waiting time; however, administrative processes partially mediate healthcare provider attitude on patient waiting time. Based on the developed framework, reducing patient waiting time in radiology can be achieved by increasing the punctuality of the healthcare providers, managing workers' attitudes, and administrative and patient workflow systems’ efficiency.